(6/x-4)/(2x-3)=0

Simple and best practice solution for (6/x-4)/(2x-3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6/x-4)/(2x-3)=0 equation:


D( x )

x = 0

2*x-3 = 0

x = 0

x = 0

2*x-3 = 0

2*x-3 = 0

2*x-3 = 0 // + 3

2*x = 3 // : 2

x = 3/2

x in (-oo:0) U (0:3/2) U (3/2:+oo)

(6/x-4)/(2*x-3) = 0

(6*x^-1-4)/(2*x-3) = 0

6*x^-1 = 4 // : 6

x^-1 = 2/3

-1 < 0

1/(x^1) = 2/3 // * x^1

1 = 2/3*x^1 // : 2/3

3/2 = x^1

x = 3/2

x in { 3/2}

x belongs to the empty set

See similar equations:

| 10y-6=4y+8 | | 8h=26 | | 7-(2z-5)=6-3z | | 2/3y+v=x | | v-9=214 | | 16+8x=25+15+3 | | -13x-13=2x-46 | | 220=4(-2+7x)+4 | | y=2/3(7)+4 | | -8(1+7m)=384 | | 0=4(4t^2+16t-7) | | 3.50+2.50x=25 | | -15+m/4=-11 | | -11n+16=-10n-5 | | -4(2-c)=12 | | -3(4r+-8)=-36 | | 49/98=a/112 | | 2/5+4/7 | | y=2/3(5)+4 | | 13.95x+1.95=85.95 | | (-2/x-3)+(3/x+3)=(-12/x^2-9) | | -7-y-y=-1 | | Ab+3c=2 | | r-5.20=3.50 | | 0.3(x+80)+1.5x=105 | | n/3-10=-6 | | y=(c-d)x+6 | | -4(x-6)=-(x-7) | | 4/5x-3=x-1/3 | | x+24+4x=-21-4x-27 | | 7y=-7y | | 8(x-3)+6= |

Equations solver categories